Pengembangan Aplikasi Ekstraksi KTP dan Reverse Geocoding pada Perangkat Bergerak untuk Verifikasi dan Validasi Data Pendaftar Data Terpadu Kesejahteraan Sosial (DTKS) - RE. Miracle Panjaitan; Bayu Rahayudi; Dian Eka Ratnawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Based on the 1945 Constitution of the Republic of Indonesia, the state is responsible for caring for the poor to meet the basic needs of humanity. The resources of social welfare in villages, assist the process of collecting data and verifying and validating the data of the poor. The results of the verification and validation are reported to the regent/mayor, then submitted to the governor, then forwarded to the Minister. Data that has been verified and validated must be based on information technology and integrated under the responsibility of the Minister. Integrated data belonging to the Ministry of Social Affairs is called the Integrated Data on Social Welfare (DTKS) and is used as a reference for the provision of Social Assistance (BANSOS). In fact, many recipients of Social Assistance (BANSOS) were found who should not be the target of this work program of the Ministry of Social Affairs. Researchers developed an ID card extraction and reverse geocoding application to help the verification and validation process, namely by matching the address obtained from the KTP extraction results with the location of the reverse geocoding results when taking photos of the ID card. This address matching is done by utilizing the Google Vision and Geocoder libraries. If the addresses match, then the DTKS registrant verification process can continue. If the addresses do not match, the DTKS registrant verification process cannot continue. This system was tested 10 times, with 5 experiments at the exact location with the ID card address and 5 at different locations with the ID card address. The success rate of this system trial is 95,7%.